Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1590/0074-0276130438
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in insect disease vectors

Abstract: Organisms from bacteria to humans have evolved under predictable daily environmental cycles owing to the Earth’s rotation. This strong selection pressure has generated endogenous circadian clocks that regulate many aspects of behaviour, physiology and metabolism, anticipating and synchronising internal time-keeping to changes in the cyclical environment. In haematophagous insect vectors the circadian clock coordinates feeding activity, which is important for the dynamics of pathogen transmission. We have recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 133 publications
(156 reference statements)
2
67
0
1
Order By: Relevance
“…Thus, the adaptation of the daily activity patterns to different environmental conditions can be easily observed in flies, although individual animals are relatively short‐lived and do usually not experience several seasons (only the individuals that overwinter experience autumn, winter, and spring). The great advantage of studying flies is that the molecular and neuronal mechanisms of the circadian clock are well‐understood in D. melanogaster (see King & Sehgal, this issue) and start to emerge also in other Diptera (Bazalova & Dolezel, ; Bertolini et al., ; Codd et al., ; Gentile, Rivas, Meireles‐Filho, Lima, & Peixoto, ; Gesto et al., ; Kaiser et al., ; Kyriacou, ; Meireles‐Filho & Kyriacou, ; Meuti, Stone, Ikeno, & Denlinger, ; Noreen, Pegoraro, Nouroz, Tauber, & Kyriacou, ; Rivas et al., ; Rund, Hou, Ward, Collins, & Duffield, ). In D. melanogaster , recent studies have shown that M and E activity bouts are reflected by Ca 2+ rhythms in the relevant clock neurons controlling M and E activity, respectively (Liang, Holy, & Taghert, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the adaptation of the daily activity patterns to different environmental conditions can be easily observed in flies, although individual animals are relatively short‐lived and do usually not experience several seasons (only the individuals that overwinter experience autumn, winter, and spring). The great advantage of studying flies is that the molecular and neuronal mechanisms of the circadian clock are well‐understood in D. melanogaster (see King & Sehgal, this issue) and start to emerge also in other Diptera (Bazalova & Dolezel, ; Bertolini et al., ; Codd et al., ; Gentile, Rivas, Meireles‐Filho, Lima, & Peixoto, ; Gesto et al., ; Kaiser et al., ; Kyriacou, ; Meireles‐Filho & Kyriacou, ; Meuti, Stone, Ikeno, & Denlinger, ; Noreen, Pegoraro, Nouroz, Tauber, & Kyriacou, ; Rivas et al., ; Rund, Hou, Ward, Collins, & Duffield, ). In D. melanogaster , recent studies have shown that M and E activity bouts are reflected by Ca 2+ rhythms in the relevant clock neurons controlling M and E activity, respectively (Liang, Holy, & Taghert, , ).…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with the conservation of core clock genes, our data suggest that D. pulex maintain a molecular clock with similar architecture to those studied in other eukaryotic organisms (Partch, Green, & Takahashi, ; Tilden et al., ). Of note, the expression levels of per and clk in our control population closely resemble the expression of these genes in mosquitoes ( Anopheles gambiae ), relevant as the circadian rhythm of D. pulex is thought to be more like that of butterflies and mosquitos than that of Drosophila (Bernatowicz et al., ; Meireles‐Filho & Kyriacou, ; Rund et al., ; Tilden et al., ).…”
Section: Discussionmentioning
confidence: 64%
“…Of note, the expression levels of per and clk in our control population closely resemble the expression of these genes in mosquitoes (Anopheles gambiae), relevant as the circadian rhythm of D. pulex is thought to be more like that of butterflies and mosquitos than that of Drosophila (Bernatowicz et al, 2016;Meireles-Filho & Kyriacou, 2013;Rund et al, 2016;Tilden et al, 2011).…”
Section: Discussionmentioning
confidence: 73%
“…activity change due to changes in their circadian rhythms by external factors such as light. 25 The number of Aedes spp. increased in the dormitory at night as students spend time at the dormitory at night, and electrical lighting attracts the mosquito.…”
Section: Discussionmentioning
confidence: 99%